Pedagogical Support and Learning Achievements in the English Area in Secondary Level Students, Educational Institution Full School Day “Juan Pablo Vizcardo y Guzman” – Lima - Julca Estelo, Rosa Beatriz (2024)
The purpose of the research was to determine the relationship between pedagogical support and the level of English language learning in high school students of the Full-Day School E.I. "Juan Pablo Vizcardo y Guzmán" in Lima. The approach of the study was quantitative in nature, non-experimental and descriptive design. population of interest was made up of 04 managers, 07 English teachers and 200 students from the 4th - 5th grades of secondary education. The sample was selected in a non-probabilistic way, including all managers and teachers, as well as 133 students. A survey was used to measure the first variable, while to evaluate learning achievement in English, a documentary review was carried out and official grade records were used. The results revealed a significant and high positive correlation (Rh= 0.891) between variables. Consequently, it was deduced that pedagogical support is positively related to English language learning.